The independent and interactive effects of heavy metal pollution and vitamin D deficiency on early kidney injury indicators: analysis of the National Health and Nutrition Examination Survey 2001–2004 - Shuhui Jing; Yuan Ge; Juan Pan; Pei Chang; Xi Qiao (BMC Public Health)
Abstract Background Heavy metals (e.g., cadmium, lead, mercury, etc.) can infiltrate the human body via diverse routes, with a propensity to accumulate in the kidney cortex, thereby precipitating kidney dysfunction. Vitamin D has been implicated in mitigating the oxidative stress and inflammatory reactions triggered by heavy metal exposure. However, the interplay between heavy metal toxicity and vitamin D deficiency in the context of incipient kidney injury remains an underexplored area of research. Methods Utilizing data from the National Health and Nutrition Examination Survey spanning from 2001 to 2004, Our methodology leveraged spline smoothing within the framework of generalized additive models to more vividly elucidate the impact of heavy metal exposure and serum vitamin D levels on the trajectory of early kidney injury biomarkers (including albumin-to-creatinine ratio, β-2 microglobulin (B2M), cystatin C (CYST), and estimated glomerular filtration rate (eGFR) (serum creatinine(SCr)-based(eGFR), CYST-based eGFR, and SCr-CYST-based eGFR). Furthermore, we conducted an interaction analysis to assess the combined effects of heavy metal exposure and vitamin D deficiency on early kidney injury. Results The cohort comprised 2,422 adults. Our results indicated that cadmium levels were positively correlated with B2M, CYST, and negatively correlated with eGFRc, eGFRs. Similarly, lead levels showed a positive correlation with ACR, B2M, and CYST, and negative correlation with eGFRc, eGFRc&s. In contrast, mercury levels were negatively correlated with B2M, CYST and positively correlated with eGFRc. In addition, there was an interaction between lead exposure and vitamin D deficiency in early kidney injury indicators (P for interaction: B2M: 0.028, CYST: 0.038, eGFRc&s: 0.011). Conclusions This study suggests a correlation between exposure to cadmium and lead and an increased risk of early kidney injury. It highlights the potential importance of targeted vitamin D supplementation and reduction in lead exposure in mitigating early kidney injury. However, these findings warrant validation through further prospective research.